2001
DOI: 10.1111/j.1469-7793.2001.0147j.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the role of reactive oxygen species in glutamate neurotoxicity in rat hippocampal neurones in culture

Abstract: Exposure of hippocampal neurones to glutamate at toxic levels is associated with a profound collapse of mitochondrial potential and deregulation of calcium homeostasis. We have explored the contributions of reactive oxygen species (ROS) to these events, considered to represent the first steps in the progression to cell death. Digital imaging techniques were used to monitor changes in cytosolic Ca2+ concentration ([Ca2+]c; fura‐2FF) and mitochondrial potential (Δψm; rhodamine 123); rates of ROS generation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 51 publications
(78 reference statements)
3
90
2
Order By: Relevance
“…Several of the drugs used in studying the mechanisms of organic anion transport, such as furosemide, piretamide, and bumetanide, as well as niflumic and flufenamic acids, appear to block NMDA-induced currents by binding to the NMDA-receptor (91), a finding that often is neglected. Similarly, it was recently reported that combinations of antioxidants such as TEMPO, catalase, trolox, and ascorbate had profound blocking effects on NMDA currents (92). In our experiments, we have used concentrations of drugs that have been shown effective against their supposed single targets in other studies.…”
Section: Discussionmentioning
confidence: 95%
“…Several of the drugs used in studying the mechanisms of organic anion transport, such as furosemide, piretamide, and bumetanide, as well as niflumic and flufenamic acids, appear to block NMDA-induced currents by binding to the NMDA-receptor (91), a finding that often is neglected. Similarly, it was recently reported that combinations of antioxidants such as TEMPO, catalase, trolox, and ascorbate had profound blocking effects on NMDA currents (92). In our experiments, we have used concentrations of drugs that have been shown effective against their supposed single targets in other studies.…”
Section: Discussionmentioning
confidence: 95%
“…Single cell analysis of cerebellar granule neurons has demonstrated a significant increase in superoxide only upon induction of DCD, and cell permeable antioxidants were not able to delay DCD [14]. A combination of antioxidants in hippocampal neurons similarly did not prevent mitochondrial depolarization or DCD but despite this conferred significant protection of cell viability [13]. Limiting the ROS-mediated damage by antioxidants is thus one potential pharmacological target and mPTinhibition another, although the pathways may intertwine due to ROS-induced ROS release [43].…”
Section: Discussionmentioning
confidence: 97%
“…Excitotoxicity is a pathological feature of both acute and chronic neurodegenerative conditions [7][8][9]. Increased ROS production from mitochondria has been demonstrated following NMDA receptor stimulation in models of excitotoxicity and has also been coupled to mitochondrial loading of calcium [10][11][12][13][14][15]. However, the mechanism linking mitochondrial calcium loading and ROS production is currently unresolved [15][16][17], and studies in isolated brain mitochondria have yielded diverging results regarding the effect of calcium on mitochondrial ROS generation [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of mitochondrial bioenergetic function in cultured neuronal models of glutamate excitotoxicity have emphasized the importance of three primary mitochondrial functions -ATP synthesis, Ca 2+ sequestration and the generation and detoxification of reactive oxygen species (Stout et al 1998;Castilho et al 1998Castilho et al , 1999Ward et al 2000;Vergun et al 2001;Wang and Thayer 2002). These processes are closely interlinked via the proton electrochemical potential gradient or its major component, the mitochondrial membrane potential (Dw m ).…”
mentioning
confidence: 99%
“…In particular, while the ability of pro-oxidants to facilitate glutamate-induced neuronal cell death is well established (e.g. Coyle and Puttfarcken 1993;Scanlon and Reynolds 1998), there are conflicting reports on the effectiveness of antioxidants in protecting cultured neurons against glutamate-induced cytoplasmic delayed Ca 2+ dysregulation (DCD) (Patel et al 1996;Castilho et al 1999;Li et al 2001;Vergun et al 2001). In the light of this, it is important to re-examine the hypothesis (Dugan et al 1995;Reynolds and Hastings 1995;Atlante et al 1996;Sengpiel et al 1998;Castilho et al 1999) that mitochondrial accumulation of Ca 2+ entering the cell via the NMDA receptor leads to increased mitochondrial generation of ROS, and that this is primarily responsible for DCD.…”
mentioning
confidence: 99%